Architectural enhancement project and cultural landscape of Cape Espichel - Fátima Fernandes (Joelho)
Challenging the conventional idea that leads to think that heritage is confined to the historic centre or classified heritage, we consider necessary to extend the concept to all those spaces loaded with values, architectural and landscape qualities necessary to man and future civilizations.